The legacy of Norbert Giambiasi to the University of Corsica: from behavioral testing to DEVS fault simulation. (June 2022) - Santucci, JF; Capocchi, L
The paper delivers a tribute to Professor Giambiasi by pointing out how the work and ideas stemming from the research performed under his umbrella in the 1980s on behavioral testing has been an inspiration for the research around DEVS formalism at the University of Corsica in the late 1990s and the beginning of the new century. The paper retraces how Giambiasi's heritage allowed researchers at the University of Corsica to go from behavioral and hierarchical testing to DEVS fault simulation.